The Influence of Innovative Learning Methods and Reading Interest on the Learning Outcomes of Students' Aqidah Akhlak Lessons - Aprilia Anis Santrika; Achmad Ridlowi; Okta Maya Fitri (STAI MA'ARIF MAGETAN, INDONESIA, 2025)
This study aims to analyze the influence of innovative teaching methods and reading interest on students' learning outcomes in the Aqidah Akhlak subject at MTs Ma’arif 017 Kalikuning. The background of the research is based on the low student achievement, which is influenced by conventional teaching approaches and a lack of reading interest. This research employs a quantitative approach with an explanatory method and an associative correlational design. The sample consists of all eighth-grade students, totaling 60 participants, selected through total sampling. The instruments used include a Likert-scale questionnaire to measure students’ perceptions of teaching methods and reading interest, along with documentation of their academic achievement. Data analysis was conducted using multiple linear regression with the assistance of SPSS. The findings reveal that both innovative teaching methods and reading interest have a positive and significant effect on students’ learning outcomes, both partially and simultaneously. Partially, innovative teaching methods have a significant influence with a t-value of 2.491 and a significance level of 0.016, while reading interest shows a stronger effect with a t-value of 5.920 and a significance level of 0.000. The F-test result shows an F-value of 24.353 (sig. 0.000), indicating a significant simultaneous influence. The coefficient of determination (R²) is 0.479, meaning that the two independent variables explain 47.9% of the variation in learning outcomes. This study highlights the importance of innovative pedagogical approaches and the strengthening of a literacy culture in enhancing the effectiveness of Aqidah Akhlak learning. Teachers are encouraged to continuously develop creative teaching strategies and foster students’ reading interest through a supportive learning environment. Future studies may consider additional variables such as family support or the integration of digital technology.